Morts invisibles versus morts mis en scène ? - Kinda Chaib (Université de Provence, 2019)
In South Lebanon, some martyrs fallen as political movements’ fighters are vividly shown, while some others are hidden. The first ones died fighting under the banner of nowadays dominant political movements as the second ones died under the banner of forgotten movements, decades ago. In the village, the cemetery is the place where these forgotten memories come up and emerge despite the homogenizing process undertaken by the Lebanese Hizbullah (among others) since the 80’s. Here, one can observe traces of what only the elderly can remember. In this paper I will focus on one south Lebanese village’s cemetery, Z., to propose leads for a social history of rural Lebanon eclipsed by the dominant collective memory. By analysing the cemetery, we can highlight a “feuilleté of memories” and discover tracks of forgotten histories.